Model Pengembangan Industri Kreatif Berbasis Syariah Di Provinsi Banten - Tri Harjawati (Al Maal: Journal of Islamic Economics and Banking, 2020)
This research is about the development of sharia-based industries in Banten Province. The goal is to find out how it’s developed and Development Model. The method used descriptive qualitative, data sources obtained from primary and secondary data. Technical analysis of data uses the interactive analysis model of Miles and Huberman. The results of the study indicate that the Development of Sharia-Based Creative Industries in Banten Province is still in the stage of drafting regulations and policies for Halal industrial zones. But indirectly the implementation technique has been running for the culinary and fashion sector (Muslim clothes). However, for future targets, the Development of Sharia-Based Creative Industries is more towards empowering Islamic boarding schools through entrepreneurs so they can create santripreneur. It’s can become centers of product excellence and centers of Islamic civilization. The Sharia-based Creative Industry Development Model in Banten Province is the form of buildings consisting of foundations, buildings and taps based on Islamic sharia boundaries. For the foundation in the form of creative beings, training can increase knowledge and creativity and the pillars consist of Industry, Technology, Natural Resources, Institutions and Financial Institutions. Tap here is the main actor, which consists of scholars/ communities, business people, and localgovernment.